PENDAYAGUNAAN DANA WAKAF PADA PROGRAM WATER ACTION FOR PEOPLE DI LEMBAGA BADAN WAKAF AL QURAN YOGYAKARTA PERSPEKTIF MAQASID SYARIAH - Darnis Darnis (Millah: Journal of Religious Studies, 2019)
Basic needs of people for clean water and a healthy environment are very fundamental. In reality there are still many remote areas suffering from the clean water crisis. In response, the Indonesian Ulama Council has issued a fatwa regarding the utilization of zakat, infaq, alms and endowments for the construction of clean water facilities as a form of implementation of sharia maqashid. One of the philanthropic institutions that also has a purpose for the social benefit is the institution of the Qur'an Waqf Agency. Through the Water Action for People program, the Alquran Waqf Agency has allocated the endowments for clean water facilities to help the areas experiencing clean water drought. This study aimed to observe the utilization of waqf funds in the Water Action for People program implemented by the Yogyakarta Alquran Waqf Agency as well as the perspective of Sharia Maqasid for these practices. This study used qualitative methods with normative and sociological approaches. The technique to determine the informants used referred to the "purposive sampling" technique. Data collection techniques used in this research included observation, interviews and documentation. The data analysis was conducted by means of Data Collection, Data Condensation, Data Display, and Conclusion. The results of this research showed that the utilization of water action for people has been in line with the utilization concepts as developed by the Directorate of Waqf Utilization for example in the aspects of benefit permanence, accountability, professional management and justice. In terms of the Sharia Maqasid the water action for people program had a very positive impact on beneficiaries, such as in keeping hifzhun din, hifzhunafs, hifzhu al-akl, hifzhu al-nasab, and hifzhu al-mal. Keywords: Al quran Waqf Agency, Utilization, Cash Waqf, Maqasid Syariah.